Perceptions of clinical leadership in the St John Ambulance Service in WA - Stanley, David; Cuthbertson, J.; Latimer, Karen (Australian College of Ambulance Professionals, 2012)
This article outlines a study aimed at identifying how clinical leadership is perceived by paramedics and ambulance personnel and the effectiveness and consequences of the application of clinical leadership in out-of-hospital care delivery. The research was conducted in Western Australia with a questionnaire distributed via in-service training sessions to St. John Ambulance operational staff between February 2010 and November 2010. Problem: To identify how clinical leadership is perceived by paramedics in the course of their everyday work and the effectiveness and consequences of the application of clinical leadership in out-of-hospital care delivery. Methods: A questionnaire was distributed via in-service training sessions to St. John Ambulance operational staff in WA between February 2010 and November 2010 (n = 250). The methodological principals of the study were based on phenomenology, with a mixed methods approach. Analysis of the quantitative data was via SPSS software and the qualitative data was analysed by spread sheet and word documents.Results: Most respondents recognised that clinical leaders were involved in team work, the generation of new ideas, effective communication and involved others appropriately. While clinical experience was valued highly, research skills or qualifications were less well recognised as an aspect of a clinical leader. What mattered was that the values of the clinical leaders were matched by their actions and abilities. Many saw clinical leaders as teachers or guides. Most saw clinical leaders as able to influence care, but only half recognised their ability to influence organisational issues. Clinical leaders were seen to be visible role models, clinically experienced, approachable, knowledgeable, driven by their desire to provide high quality care and change practice. They were seen to be team members who make decisions often under pressure. Conclusion: It is hoped that with a better understanding clinical leadership and how it is perceived by paramedics and ambulance officers they will be able to play a more effective part in service improvement, the implementation of a quality agenda and impact positively on out-of-hospital care delivery. As well, a better understanding of clinical leadership may support a more responsive and effective ambulance service where the focus can remain on the clinical aspects of the paramedic's role.